Progressive Muscle Relaxation Therapy to Increase Muscle Strength in the Elderly with Post-Non Hemorrhagic Stroke at Adiwerna Tegal - Putra Satria, Ramadhan; Jumrotun Ni’mah; Farkhani (International Journal of Midwifery and Health Sciences, 2024)
Background: Stroke is the second highest cause of death in the world and the highest cause of disability in the world. The 2018 RISKESDAS results showed that the prevalence of stroke cases in Indonesia was 10.9%. Stroke has a lot of impact on patients and their families. Progressive muscle relaxation therapy is one of the therapies that can be used to increase the muscle strength of the elderly after a non-hemorrhagic stroke by relaxing and tensing the body’s muscles. Purpose: The study aimed to apply progressive muscle relaxation therapy to increase muscle strength in the elderly after a non-hemorrhagic stroke. Method: The study was descriptive research with a case study approach. The subjects were the elderly after a non-hemorrhagic stroke. Data were obtained through interviews, observations, physical examinations, and documentation studies. Result: Before applying the therapy, the patients’ muscle strength value was 3; the patients’ hand grip was weak. After doing the therapy for 3 days, the patients’ muscle strength was still 3, but the patients’ hand grip felt tight. Conclusion: The elderly people after non-hemorrhagic stroke are recommended to do progressive muscle relaxation therapy once a day with a duration of 15-20 minutes to stimulate the muscles so that it can increase their muscle strength.